Online illegal wildlife trade in Indonesia: strengthening the regulatory framework and law enforcement - Krismanko Padang; Nuruliawati; Zahrah Afifah; Muhammad Irfan Andriansyah; Andina Auria Dwi Putri; Nur Hafizoh; Irma Hermawati; Ade Indah Muktamarianti; Syaras Yulianti; Niken Wuri Handayani; Sofi Mardiah (Oryx)
E-commerce applications have significantly changed how people transact with each other. This includes digital advances that drive illegal wildlife trade. In Indonesia, the Conservation Act of 1990 was enacted before the internet revolution and does not, therefore, adequately cover online illegal wildlife trade. In this study we identified wildlife traded illegally through advertisements published by five large national e-commerce companies and one social media platform operating in Indonesia, using 39 keywords. We also analysed data on wildlife cybercrime court case outcomes, associated criminal networks and their modus operandi. Over 12 months, we found 996 advertisements for wildlife and wildlife products, including of 45 nationally protected species, from 421 accounts. Amongst the six platforms monitored, Facebook Marketplace had the highest illegal wildlife trade traffic. We found that those prosecuted for online illegal wildlife trade were given low sentences. Our analysis of wildlife legislation, focus group discussions and expert interviews showed that the Government of Indonesia Trade Law (2014) and Law on Electronic Information and Transactions (2008) cannot be used to prosecute online illegal wildlife trade cases because these laws do not acknowledge regulations for protected species. Our study emphasizes the urgency of revising the Conservation Act and changing the definition of trade to include advertisements of protected species. We recommend development of screening tools for advertisements and accounts on e-commerce platforms, review of community/user guidelines to prohibit trade of protected species, and strengthening the approach of combining multi-context laws with stakeholder cooperation to prosecute online illegal wildlife trade cases.